Optoelectronic Devices: Solution‐Growth Strategy for Large‐Scale "CuGaO2 Nanoplate/ZnS Microsphere" Heterostructure Arrays with Enhanced UV Adsorption and Optoelectronic Properties (Adv. Funct. Mater. 23/2017). (June 2017) - Li, Yanmei; Song, Yun; Jiang, Yingchang; Hu, Mingxiang; Pan, Zhichang; Xu, Xiaojie; Chen, Hongyu; Li, Yuesheng; Hu, Linfeng; Fang, Xiaosheng
Abstract : In article number1701066, Linfeng Hu, Xiaosheng Fang, and co‐workers rationally design large‐scaled CuGaO2 nanoplate/ZnS microsphere p‐n arrays through a facile low‐temperature solution strategy associated with an oil‐water interfacial self‐assembly approach. The ZnS microspheres are grown on the CuGaO2 thin‐film through an Ostwald ripening mechanism, and the as‐designed CuGaO2 nanoplate/ZnS microsphere heterostructure arrays exhibit drastically enhanced optoelectronic properties in UV‐light sensitivity.